Quantificação de biomassa aérea e determinação do modelo arquitetural dos regenerantes de Cordia ecalyculata Vell. em um fragmento secundário de floresta estacional decidual, no município de Silveira Martins, RS - Sousa, Thais Gois de (2021)
The aim of the study was to define the architectural model of these regenerants from a Cordia ecalyculata (Vell.) population and to estimate the aerial biomass of those selected from the selected population. In a particular area, municipality of Silveira Martins - RS, a census was carried out in an area of approximately 0.5 ha, with application of the intentional non-probabilistic sampling method by free walking, having as sample unit 21 regenerating individuals of C. ecalyculata. The plants were visually analyzed in the field, considering morphological and architectural criteria, to evaluate the aerial biomass production, a sampling of the branches was carried out. The following variables were measured in the laboratory in the branches: Diameter of the base of the branches (DB); Total length (CT), sum of the lengths of the branch axes compartments; and Dry biomass of branches (BS), obtained in an oven with air circulation at a temperature of 50 ºC for 72 hours until reaching constant weight. The relationship between dry biomass (BS) and the branching pattern of the species was studied using the GLM procedure. To verify the adequacy of the BS estimating models, the residual analysis was used in a graph: observed BS x evaluated BS. The species was published according to the architectural model of Prévost. The dry biomass of the branches presents a close relationship with the evaluated branching classes. The mean values of dry biomass of branches for classes A2 (1.34g), A3 (3.33g) and A4 (8.77g) can be used to estimate the volume of a particular branch. The dry biomass (BS) of shoots of Cordia ecalyculata regenerants can be estimated with high precision and quality using the branch dimensions. The quadratic transformation of DB was superior, with model: BS = 43.57 DB² - 0.6221. CT shown- lower for BS estimation, with BS model = 0.0675 CT - 1.0433. The transformed variable (DB2CT)0,5 satisfactorily estimated the BS, generating a model: BS = 1.8092 (DB²CT) 0,5 - 0.9852. Concluding that the characteristic branching pattern, which particularizes a type, can be used for the use of dry biomass of branches and leaves (BS) in forest inventories.